WAYS OF FORMING THE MORAL AND MORAL QUALITIES OF LEADERS AND SPECIALISTS OF VOCATIONAL EDUCATIONAL INSTITUTIONS (International journal of artificial intelligence, 2025)
The article analyzes the spiritual and moral qualities of leaders and specialists of professional educational institutions on the basis of scientifically and theoretically clear proposals, recommendations and conclusions. The pedagogical methods of the management skills of leaders of professional educational institutions and the skills of pedagogical staff in the teaching process, pedagogical ethics, and spiritual qualities are substantiated.